Involvement of cytochrome P450 enzymes in inflammation and cancer: a review - Stipp, Maria Carolina; Acco, Alexandra (Cancer chemotherapy and pharmacology, 2021)
Cytochrome P450 (CYP) enzymes are responsible for the biotransformation of drugs, xenobiotics, and endogenous substances. This enzymatic activity can be modulated by intrinsic and extrinsic factors, modifying the organism’s response to medications. Among the factors that are responsible for enzyme inhibition or induction is the release of proinflammatory cytokines, such as interleukin-1 (IL-1), IL-6, tumor necrosis factor α (TNF-α), and interferon-γ (IFN-γ), from macrophages, lymphocytes, and neutrophils. These cells are also present in the tumor microenvironment, participating in the development of cancer, a disease that is characterized by cellular mutations that favor cell survival and proliferation. Mutations also occur in CYP enzymes, resulting in enzymatic polymorphisms and modulation of their activity. Therefore, the inhibition or induction of CYP enzymes by proinflammatory cytokines in the tumor microenvironment can promote carcinogenesis and affect chemotherapy, resulting in adverse effects, toxicity, or therapeutic failure. This review discusses the relevance of CYPs in hepatocarcinoma, breast cancer, lung cancer, and chemotherapy by reviewing in vitro, in vivo, and clinical studies. We also discuss the importance of elucidating the relationships between inflammation, CYPs, and cancer to predict drug interactions and therapeutic efficacy.